Multimorbidity and the use of health services in the Brazilian population: National Health Survey 2019 - Ana Sara Semeão de Souza (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective To describe the prevalence of health service use due to multimorbidity according to sociodemographic and health characteristics of the Brazilian population; to analyze the relationship between multimorbidity and the use of health services. Methods This was a cross-sectional study using data from the 2019 National Health Survey. The outcomes were seeking health services in the last 15 days, medical consultation and hospitalization in the previous 12 months. Multimorbidity was defined as ≥ 2 chronic diseases. Associations were assessed using Poisson regression. Results Of the 81,768 individuals, prevalence of seeking health services among individuals with multimorbidity was 38.0% higher (95%CI 1.31;1.45), medical appointments, 11.0% higher (95%CI 1.10;1.12), and 56.0% higher for hospitalizations (95%CI 1.44;1.70), compared to those without multimorbidity. This relationship was higher for seeking health services and medical appointments among male. Conclusion The use of health services was higher among those with multimorbidity, but different between the types of health services used and sexes.